2019
DOI: 10.1371/journal.pone.0221990
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Carnivore protoparvovirus 1 in free-living leopard cats (Prionailurus bengalensis chinensis) and its association with domestic carnivores in Taiwan

Abstract: Carnivore protoparvovirus 1 (CPPV-1) is widespread among free-living carnivores, and CPPV-1 infection may directly or indirectly impact on the population of endangered carnivore species. In this study, we used molecular screening of viral capsid protein 2 (VP2) from 2015 to 2017, to assess the prevalence of CPPV-1 infection in 9 live-trapped (LT) and 17 vehicle collision (VC)-affected free-living leopard cats ( Prionailurus bengalensis chinensis ). In addition, we conducted the phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 38 publications
2
51
0
Order By: Relevance
“…To our knowledge, CPPV-1 and FCoV infection in free-living leopard cats has only been reported in Taiwan (6), although CPPV-1 infection has been previously reported in captive leopard cats from Taiwan and Vietnam (11, 12). The worldwide distribution of CPPV-1 has resulted in the infection of various wild carnivorous species (22, 3538).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…To our knowledge, CPPV-1 and FCoV infection in free-living leopard cats has only been reported in Taiwan (6), although CPPV-1 infection has been previously reported in captive leopard cats from Taiwan and Vietnam (11, 12). The worldwide distribution of CPPV-1 has resulted in the infection of various wild carnivorous species (22, 3538).…”
Section: Discussionmentioning
confidence: 86%
“…Our previous study found that the majority of sequences of CPPV-1 variants were identical between domestic carnivores and the leopard cats based on the partial VP2 gene sequences (6), which suggested frequent transmission of CPPV-1 between domestic and wild carnivores. In this study, we collected 2 times of leopard cat samples and we recorded several different sequence types for each CPPV-1 variant circulating in the leopard cat population (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations